Sorption of 60Co onto bentonite clay - Zether, Alexander (My University, 2021)
Spent nuclear fuel is highly radioactive, warranting adequate methods of disposal. In Sweden, SKB is constructing a final repository in Forsmark, which utilises several barriers to prevent any radioactive material from reaching nature or society. The spent fuel, held in place by ductile iron cartridges, is placed inside copper canisters, which are surrounded by bentonite clay in bedrock tunnels situated 500 metres underground. In the event of a canister breaking, it is important to know the behaviour of the radioactive material as it spreads. Earlier experiments, performed by SKB and at Chalmers University of Technology have studied the diffusion of the radionuclide 60Co in bentonite to find the rate of spread of the active substance. One aspect of the diffusion process is the amount of cobalt that sorbs onto the clay. By studying the sorption through the distribution coefficient, Rd, the diffusion mechanism can be better understood. In this thesis, the distribution coefficient has been studied for 60Co onto bentonite clay, by means of batch sorption in simulated groundwater, as well as water with NaClO4 and Ca(ClO4)2, at 25 oC, 50 oC and 75 oC for a period of circa two months. Samples were prepared at a solid to liquid ratio of 1:20 and the activity of the samples was measured with increasing time intervals through liquid scintillation counting. Long-term equilibrium was reached after approximately 30 days for all samples. The studied parameters, temperature and water composition, were determined to both have a significant impact on the sorption process, where temperature and ion diversity displayed positive and negative correlation, respectively, to 60Co-sorption onto bentonite. Distribution coefficient values at room temperature ranged between approximately 0.28-0.63 m3/kg at 25 oC, 1.04-2.97 m3/kg at 50 oC and 2.87-7.41 m3/kg at 75 oC.
Keywords: Cobalt; Bentonite; Batch sorption; Repository; Distribution coefficient